Role of Supply Chain Management in the Automotive Industry of the United Arab Emirates - ALHEBSI, ABDULLA RASHED (2017)
The paper studies the role of supply chain management in the automotive industry of the United Arab Emirates and its significance of the production activities. The supply chain has a direct relation with improvements of business operations and other related activities. The paper determines supply chain activities declines to productivity loss and improves logistics. The automotive industry in UAE faces the issues of supply chain activities that affect the overall performance of organizations. The research determines the risks and threats that auto industry faces in supply chain management. The identification of risks helps companies that the auto industry to formulate a policy that helps to improve supply chain activities. The common risk factors that companies in auto industry encounter involve uncertain risks such as natural calamities, terrorist attacks, loss of data and thefts. Technology has a significant role in effective supply chains operations, and lapse in technology declines the effectiveness’ of the supply chain. The supply chain disruptions lead to deteriorated performance of business activities those results in reduces revenues and profitability of organizations. Fluctuations in exchange rates and prices serve as risk factors for the ineffective supply chain. The study incorporates qualitative and quantitative research methodology. The secondary data involves scholarly databases and available literature on an electronic database. The primary data involves a survey of employees of the automotive industry in UAE. The survey involves questionnaire that seeks information from employees about the supply chain practices in organizations. The information of questionnaires provides the understanding and awareness of organizations about the role of the supply chain. The responses of employees provide information about the common risk factors that organizations face in the implementation of the effective supply chain. The statistical technique involves SPSS for assessment of participants’ responses. The results confirm the risk factors of supply chain causes implication son the supply chain. The information about risks suggests the need to address the issue of the supply chain that leads to improvements in the automotive industry of UAE.